P. SOLOMITA - Pier Luigi Nervi vaulted architecture.Towards new structures - Molina, Mariano (ZARCH, 2016)
PASQUALINO SOLOMITAPier Luigi Nervi vaulted architecture.Towards new structuresBolonia, Bononia University Press, 2015, 252págs.Idioma: inglés. 36 € (tapa blanda)